Climate and Plant Phenology (Plant Age and Growth Stage) Influence of Rhopalosiphum Padi L. Abundance on Wheat Plants in Luxor Governorate, Egypt - Moustafa Mohamed Sabry Bakry; Amr M. M. Badawy; Lamiaa H.Y. Mohamed (Andalasian International Journal of Entomology, 2024)
Field experiments were conducted at El-Mattana Agricultural Research Station, Luxor Governorate, during two successive wheat growing seasons (2017/18 and 2018/19). This was to study the seasonal abundance of Rhopalosiphum padi (Hemiptera: Aphididae) on wheat plants (Giza 171 cultivar). We also investigated the effects of climate and plant phenology on the R. padi population density. Results indicated that R. padi infested wheat plants from December 17, 2017, until April 8, 2018, within the first growing season (2017/18), and from Jan. 27th, 2019, up to April 13th, 2019, within the second growing season (2018/19). The cumulative counts of R. padi in growing season one was 9486.17, and in growing season two, 3444.00 individuals. The mean population of R. padi per 10 tillers over the whole first season was 80.12 ± 7.90, and for the second season, 42.36 ± 2.96. The first season, December, January, and February, had the most favorable climate for R. padi population growth (measured during weekly inspections). In contrast, February and March were more favorable in the second season. R. padi was not detected on the wheat during the wheat maturation period within both growing seasons. The combined effects of climate and plant phenology strongly correlate with R. padi population density, with explained variance (EV) of 93.86% in the first season and 99.11% in the second season. Daily mean maximum temperature was the most influential variable explaining changes in total R. padi population, with EV 28.37%in the first season and 28.62% in the second season. The data provided here can assist in the design of Integrated Pest Management (IPM) programs for aphid control on wheat plants.